Polymeric Adsorbents: Innovative Materials for Water Treatments - Mazumder, Mohammad A. J. (Current Analytical Chemistry, 2023)
Background: Removing heavy metal ions and various organic contaminants from water (surface water, groundwater, drinking water, and wastewater) using inexpensive and readily available adsorbents is essential in all environmental and human aspects. This study aims to explore the various adsorbents with a particular emphasis on polymeric adsorbents for their applications in the removal of heavy metal ions and emerging contaminants from water. Methods: A brief review as a perspective article on polymeric adsorbents with a particular emphasis on their applications in water treatment, consequences, challenges, and relevant issues/ perspectives that need to be resolved in the future is highlighted. Results: Due to the increasing global human population with rapid urbanization, industrialization, and environmental change, removing heavy metals and emerging contaminants from water fonts has become a primary environmental concern and a huge challenge to ensure safe water supplies. This directs an utmost demand to develop various water treatment and recycling methods. Different types of adsorbents, including polymeric adsorbents, have also been discussed. The study indicates the presence and structural behaviors (e.g., functional groups, degradation, adsorption, desorption), adsorption-desorption process, regeneration, safe removal and disposal procedure, and toxicity of the adsorbents are vital to use them safely for an extended period in the application of water treatment. Conclusion: A brief discussion on adsorption, methods, various types of polymeric adsorbents, and their applications for removing organic and/or heavy metal contaminants from water and wastewater is presented in this review as a perspective article. A better understanding of the preparation of polymers from inexpensive, readily available, natural sources and toxicity issues is still needed to be considered, particularly in the human-related exposure and relevant risk on the water and wastewater treatment.
Keywords: adsorption